INFLUENCE OF SURFACTANTS ON SURFACE TENSION AND SATURATED VAPOR PRESSURE OF HYDROCARBONS - Ledovskykh, Volodymyr; Stepanov, Nikolay; Freimantal, Ekaterina (Proceedings of National Aviation University, 2014)
Results of comparative research of non-volatile additives influence on surface tension of hydrocarbons(stalagmometric method) and on saturated pressure vapor are provided. It was shown that in hydrocarbon media withincluded surfactant addition weakening of surface tension on the border of liquid and gas phases and increasing ofsaturated vapor pressure may occur. Which allows for increase of light oil products yield in primary oil refining.